Long Term Background Reference Based Satellite Video Coding - Wang, Xu; Hu, Ruimin; Wang, Zhongyuan; Xiao, Jing; Zhang, Yuhui (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2019)
Video transmission from satellites to terrestrial devices usually requires a large amount of channel resources due to the huge amount of satellite video data. Subject to limited transmission bandwidth in space environment, the video encoder for video satellite calls for higher coding efficiency. In this paper, we propose a high efficiency satellite video coding method based on long term background reference (LTBR) to eliminate redundancy caused by periodical revisit. Firstly, data of Google Earth is used to provide prior information for establishing LTBR. Then a novel intra prediction method guided by pixels' cluster information from LTBR is introduced. Experiments demonstrate that our method outperforms HEVC and H.264 , in terms of rate-distortion, BD-PSNR and BD-Rate performance.